Academic self-efficacy in Portuguese public higher education students - Ribeiro, Maria Isabel (2020)
Academic self-efficacy refers to the belief of an individual successfully attaining an academic task or achieving a specific academic goal. Self-efficacy is critical to student success because it influences the choices students make along their academic and professional path. This study aimed to determine the level of academic self-efficacy in higher education students and to verify if there were differences statistically significant, taking into account the sociodemographic variables, namely, gender, age and nationality, and the academic variables, such as scientific area, degree, course year, course with or without integrated internship and attendance regimen. To achieve these objectives, an observational, cross-sectional, quantitative and analytical study was carried out based on a random sample of 2152 individuals from a total of 8200 students enrolled, in the 2018/2019 school year, in a public higher education institution located in the Northern of Portugal. The margin of error was 1.81%. The students were aged between 17 and 52 years old. The students registered a moderate level (4.42 ± 0.092) of academic self-efficacy out of 7. It was observed that 45.5% of the students registered a high level of academic self-efficacy; 17.9% revealed a low level; and the remaining 36.6% showed a moderate level. Statistically significant differences were found in academic self-efficacy taking into account the nationality of students (p-value = 0.041). The foreign students registered a highest academic selfefficacy level. Additionally, the comparison analysis demonstrated that there were significant differences between the students' scientific area (p-value = 0.004) and attendance regimen (p-value = 0.043). It was the Technology and Management students as well as the worker students who had the highest levels of academic self-efficacy. Nationality, scientific area and attendance regimen showed to be differentiator factors of academic self-efficacy. Foreigner students, worker students and students from the technology and management scientific area showed more confidence to achieve their academic goals. In fact, students’ confidence in succeeding in their academic assignments will affect their lifelong learning. Therefore, higher education institutions should be able to improve the academic self-efficacy of students, creating innovative learning environments adapted to the needs and knowledge of their students.